(untitled) (Bangladesh Journal of Urology, 2020)
Objective:To compare the efficacy of Gemcitabine and Mitomycin C in the treatment of non muscle invasive transitional cell carcinoma of urinary bladder. Methods: This study was a randomized clinical trial conducted between the periods of November’2013 to October’2014 in the Department of Urology, Bangabandhu Sheikh Mujib Medical University (BSMMU) The patients with histopathologicaly diagnosed as non muscle invasive transitional cell carcinoma of urinary bladder after complete TURBT were included in the study. Total 54 patients were included in this study ( 27 patients in each group). Those treated with intravesical Gemcitabine were considered as experimental group and those treated with intravesical Mitomycin C (MMC) considered as control group. Intravesical Inj. Gemcitabine and Mitomycin C mg dissolved in 50 ml of normal saline and instilled into the urinary bladder through Foley urethral catheter in the considered group and kept for two hour after getting the histopathology report. Same schedule was maintained weekly for 6 weeks. All patients were followed up at 6 weeks after 1st cycle of intravesical instillation then 3 monthly for 1 year. Result : Presence of recurrence of tumour was found non-significant in Gemcitabine and Mitomycin C group (18.5% vs. 40.7%, p= 0.074). Recurrence free survival was found 81.5% patients in Gemcitabine group and that of 59.3% patients in Mitomycin group. Though there was more recurrence free survival in gemcitabine group than mitomycin group, there was no statistically significant difference. Tumour grade progression was found in 20% and 27.3% cases in Gemcitabine and Mitomycin C group respectively. On the other hand, tumour stage progression was found 40.0% and 27.3% patients in Gemcitabine and Mitomycin C group respectively. No statistically significant difference was observed between Groups (P>0.05). Haematuria, dysuria, urinary frequency, urgency and contact dermatitis were found non-statistically significant in both groups. Conclusion : Gemcitabine and Mitomycin C both drugs are effective as intravesical chemotherapy in the treatment of non muscle invasive transitional cell carcinoma of urinary bladder and have a better recurrence free survival. But, accounting statistical significance on chemopreventive activity, neither Gemcitabine nor Mitomycin C therapy showed superiority over each other. Bangladesh Journal of Urology, Vol. 22, No. 1, January 2019 p.25-29